2006
DOI: 10.1089/bfm.2006.1.263
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Group B Streptococcal Infection Related to Breast Milk

Abstract: Group B streptococcus is currently the most common cause of sepsis and meningitis in newborns. How should mothers whose breast milk cultures show growth of this microorganism be managed regarding breastfeeding? This case study discusses the possible transfer of group B streptococcus to a preterm infant from mother's milk. It also describes the process that was taken to preserve the breastfeeding experience while the infant was treated. The questions provoked during this investigation prompted the authors to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…16 There are reports of recurrent infections in premature infants associated with isolation of the same organism in the milk. 7,9,17 Our data suggest that simultaneous occurrence of positive cultures in both milk and infant may signify common exposure of infant and mother to that organism. It is difficult to presume only unidirectional transmission from mother to infant.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…16 There are reports of recurrent infections in premature infants associated with isolation of the same organism in the milk. 7,9,17 Our data suggest that simultaneous occurrence of positive cultures in both milk and infant may signify common exposure of infant and mother to that organism. It is difficult to presume only unidirectional transmission from mother to infant.…”
Section: Discussionmentioning
confidence: 77%
“…3,4 Although case reports suggest that milk may be a source of infection, fewer infections and infection-related events are reported in extremely premature infants if fed their mothers' milk (MM). [5][6][7][8][9][10] Nevertheless, some clinicians order bacterial cultures of MM and await the results of the screening before allowing the milk to be fed. 11 We determined serial microbial cultures of expressed MM.…”
Section: Introductionmentioning
confidence: 99%
“…However, Olver et al described cases of GBS infection in preterm infants fed with maternal milk via nasogastric tube alone [9]. Prematurity is a recognized predisposing factor to GBS infection, although breast milk transmission was also described in term infants [4].…”
Section: Discussionmentioning
confidence: 99%
“…If breast milk is positive for GBS, adequate antibiotherapy should also be prescribed for the mother. Byrne et al reported that it is possible to give the mother the opportunity to continue breastfeeding as desired; she can be encouraged to maintain her milk supply by pumping and discarding milk until appropriate treatment is completed and negative breast milk cultures are obtained [4].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Most such reports are single or small case series documenting an infant(s) with late-onset sepsis and the isolation of the same organism from the infant's mother's breastmilk. Common themes in these cases that may alert clinicians to this problem include recurrent episodes of sepsis with the same organism in a single patient, occurrence of sepsis with the same organism in siblings (twins, triplets), or late-onset sepsis and clinical symptoms of mastitis in the mother.…”
mentioning
confidence: 99%